Effect of bio-banding on physiological and technical-tactical key performance indicators in youth elite soccer - Lüdin, D.; Donath, L.; Cobley, S.; Romann, M. (European Journal of Sport Science, 2022)
Bio-banding has been introduced to reduce the impact of inter-individual differences due to biological maturation among youth athletes. Existing studies in youth soccer have generally examined the pilot-testing application of bio-banding. This is the first study that investigated whether bio-banded (BB) versus chronological age (CA) competition affects reliable physiological and technical-tactical in-game key performance indicators (KPIs) using a randomized cross-over repeated measures design. Sixty-five youth elite soccer players from the under-13 (U13) and under-14 (U14) age category and with maturity offsets (MO) between -2.5 and 0.5 years, competed in both a BB and CA game. For statistical analysis, players were divided into four sub-groups according to CA and MO: U13MOlow (CA = 12.7, MO = -1.4), U13MOhigh (CA = 12.7, MO > -1.4), U14MOlow (CA > 12.7, MO = -1.4), U14MOhigh (CA > 12.7, MO > -1.4). The two-factor mixed ANOVA revealed significant (p < .05) interactions between competition format and sub-group for the KPIs high accelerations (Eta2p = .176), conquered balls (Eta2p = .227) and attack balls (Eta2p = .146). Especially, U13MOhigh (i.e. early maturing players) faced a higher physiological challenge by having more high accelerations (|d| = 0.6) in BB games. Notably, U14MOlow (i.e. late maturing players) had more opportunities to show their technical-tactical abilities during BB games with more conquered balls (|d| = 1.1) and attack balls (|d| = 1.6). Affected KPIs indicate new challenges and learning opportunities during BB competition depending on a player`s individual maturity status. Bio-banding can beneficially be applied to enhance the talent development of youth elite soccer players.